TINGKAT PARTISIPASI ANGGOTA P3A DALAM PROGRAM PENGEMBANGAN JARINGAN IRIGASI (PJI) DI KELURAHAN FAJAR ESUK KECAMATAN PRINGSEWU KABUPATEN PRINGSEWU - Ayu Yuni Antika; Dewangga Nikmatullah; Rio Tedi Prayitno (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2017)
This research aims to analyze the participation level of P3A member on the irrigation network development (PJI) program and to find out the factors related to participation level of P3A member on the irrigation network development (PJI) program in Fajar Esuk Village, Pringsewu Subdistrict, Pringsewu Regency.  The location was chosen purposely in P3A Fajar Tirta Kencana with 72 samples.  This research was conducted in September 2016 using a survey method.  Data were analyzed descriptivel and used rank Spearman nonparametric statistics test.  The results showed that most of P3A membesr has low participation.  The factor related to participation level of P3A members on the irrigation network development (PJI) program in Fajar Esuk Village, Pringsewu Subdistrict, Pringsewu Regency is intencity of communication.  The faremer’s age, level of formal education, the level of knowledge about PJI program, and the level of expectations to benefit program do not have a significant relationship with the participation level of P3A members on the irrigation network development (PJI) program in Fajar Esuk Village, Pringsewu Subdistrict, Pringsewu Regency. Key words: P3A, participation, PJI program